A New Type Circular Photonic Crystal Fiber for Orbital Angular Momentum Mode Transmission - Zhang, Hu; Zhang, Wenbo; Xi, Lixia; Tang, Xianfeng; Zhang, Xia; Zhang, Xiaoguang (IEEE photonics technology letters, 2016)
We proposed a new circular photonic crystal fiber (C-PCF), which can support 14 orbital angular momentum (OAM) modes transmission, with the good features of wide bandwidth, low confinement loss, and all OAM modes at the same size. At 1.55 μm, the designed C-PCF has a very low confinement loss of 3.434 × 10 -9 dB/m for HE41 mode and a relatively low nonlinear coefficient of 3.979 W -1 km -1 for EH 31 mode. The common bandwidth for the four orders of OAM modes is as large as 560 nm (about 1.25 μm-1.81 μm), which does cover all bands of optical fiber communication. Flat dispersion (a total dispersion variation of <;46.38 ps nm -1 km -1 over a 750-nm bandwidth from 1.25 μm to 2 μm for TE 01 mode) is another feature. With all these good features, the proposed C-PCF could be a well-promising OAM fiber for mode division multiplexing in high capacity fiber communication systems.